The Development of Learning Media for 6th Grade Elementary School Solar System Courses-based on Android with Virtual Reality Technology - Aditya Nugraha Pradana; Dwi Maryono; Endar Suprih Wihidayat (Journal of Informatics and Vocational Education, 2022)
This study aims to: (1) create learning media for android-based solar system subjects with virtual reality technology and (2) determine the feasibility of learning media for android-based 6th-grade solar system subjects with virtual reality technology. Solar system learning media for Android-based 6th-grade elementary school with virtual reality technology was developed using the Luther method through 6 stages: concept, design, material collection, manufacture, testing and distribution. The concept stage determines the objectives, materials, and content of the learning media that will be developed. The design stage is determining the material and storyboard. The material collection stage includes determining learning materials, Unity 3D assets, images, audio and others that support the learning media. The manufacturing stage is making learning media according to the predetermined design and storyboard. At the testing stage, we validated the product with media experts, material experts, and users. At the distribution stage, it produces media in the form of *.apk, which is uploaded to Google Drive. The validation of learning media is seen from the assessment of media experts, material expert assessments, and user assessments. Ratings obtained from all these aspects are 91.9% from media experts, 88.3% from the material, and 71% from users. The results of the three assessments have an average of 83.7%. From these results, it can be concluded that this learning media can be used as a learning medium.